KELUARGA BERENCANA (Studi Analisis Fatwa Ali Jum’ah Dalam Kitab Al-Fatâwâ Al-Islâmiyyah) - Sri Aisyah; Zainal Azwar (UIN Imam Bonjol Padang, 2020)
The problem in this study is the existence of Ali Jum'ah's opinion about the permissibility of doing family planning in terms of (tahdîd al-Nasl) birth restriction. The objectives to be achieved in this study are to determine the factors causing Ali Jum'ah's disagreements with most muftis in Egypt regarding family planning, knowing the arguments used by Ali Jum'ah regarding family planning, and analyzing the influence of certain schools of thought on Ali Jum ' ah about family planning. The results of the study can be concluded as follows: first, the factors causing the difference in opinion between Ali Jum'ah and most muftis in Egypt regarding family planning due to differences of opinion in terms of tandzîm al-Nasl and tahdîd al-nasl, the time period for performing 'azl and the influence of the school of thought on abortion. Second, the argument used by Ali Jum'ah regarding family planning is the ability of 'azl in Islam as narrated by Bukhari and Muslim. While the ability to terminate the womb, Ali Jum'ah did not mention the arguments related to this in his fatwa. Third, Ali Jum'ah allowed 'azl not to be influenced by certain schools of thought, because in general the Imams of madzhab allowed' azl with the wife's permission. Meanwhile, Ali Jum'ah's skills regarding abortion were influenced by the Hanafi school of thought.Keywords: Family Planning, Fatwa, Ali Jum'ah, Kitab Al-Fatâwâ Al-Islâmiyyah